1983
DOI: 10.1021/bi00274a036
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of deoxyribonucleic acid sequences with homology to a cloned complementary deoxyribonucleic acid coding for rat phenobarbital-inducible cytochrome P-450

Abstract: We previously identified cDNA clones for rat cytochrome P-450 of the phenobarbital-inducible type by sequence analysis [Fujii-Kuriyama, Y., Mizukami, Y., Kawajiri, K., Sogawa, K., & Muramatsu, M. (1982) Proc. Natl. Acad. Sci. U.S.A. 79, 2793-2797]. With these cloned cDNAs as probe, the multiplicity of phenobarbital-inducible cytochrome P-450 gene in rat genome was investigated by three approaches. The first approach was the Cot analysis of the total rat liver DNA under conditions of DNA excess. With internal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…3 (1984) genes for other forms of cytochrome P-450 or divergent P450Oc genes, and further studies to identify and characterize clones in a bovine genomic library should clarify this point. In the case of the phenobarbital subset of rat liver cytochromes P-450, there appear to be six to eight genes or pseudogenes encoding several forms of cytochrome P-450 (10)(11)(12). The identification and characterization of cDNA clones specific for P-450sc provide the tools necessary to examine the mechanisms by which trophic hormones regulate the synthesis of this form of cytochrome P-450.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 (1984) genes for other forms of cytochrome P-450 or divergent P450Oc genes, and further studies to identify and characterize clones in a bovine genomic library should clarify this point. In the case of the phenobarbital subset of rat liver cytochromes P-450, there appear to be six to eight genes or pseudogenes encoding several forms of cytochrome P-450 (10)(11)(12). The identification and characterization of cDNA clones specific for P-450sc provide the tools necessary to examine the mechanisms by which trophic hormones regulate the synthesis of this form of cytochrome P-450.…”
Section: Resultsmentioning
confidence: 99%
“…Elucidation of the structure and organization of genes encoding certain xenobiotic-inducible forms of cytochrome P-450 has brought to light several interesting features including the existence of multiple genes (10)(11)(12) and unusually large mRNA molecules (13-15) as well as possible mechanisms involved in genetic regulation (11,12,(16)(17)(18)(19). However, little is known concerning the structure and organization of the genes and.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly half of these differences are contained within two short regions of relatively high (23-24%) sequence divergence that account for nearly half of the amino acid differences between the two polypeptides and are located within exon 7 ofthe cytochrome P-450e gene (17,18). These flank a more highly conserved segment encoding an "analogous tridecapeptide" observed by Ozols et al (19) in two ostensibly unrelated rabbit liver P450 isozymes, one constitutive (LM-3b) and one highly induced by phenobarbital .Recently, a series of genes distinct from the P-450e and P-450b genes but having sequence homology to cytochromes P-450b and P-450e cDNAs have been cloned and characterized (18,20). Hybridization of several of these genes to P-450e cDNA probes combined with heteroduplex analysis revealed that the region of high homology to the cytochrome P-450e gene is limited to exons 7 and 8, and possibly the intron between them (18).…”
mentioning
confidence: 94%
“…Recently, a series of genes distinct from the P-450e and P-450b genes but having sequence homology to cytochromes P-450b and P-450e cDNAs have been cloned and characterized (18,20). Hybridization of several of these genes to P-450e cDNA probes combined with heteroduplex analysis revealed that the region of high homology to the cytochrome P-450e gene is limited to exons 7 and 8, and possibly the intron between them (18).…”
Section: Introductionmentioning
confidence: 99%